The teaching of medical ethics at Southampton University Medical School. Issue 4 (December 1977) - Dennis, K J; Hall, M R
Abstract : For centuries medical schools in Britain and elsewhere had a fairly static curriculum based on what might be called the 'three Rs' of medicine, and consequently had to make room for new subjects as the need arose in a fashion which was sometimes makeshift. However, Southampton University has only had a medical school for six years, and therefore their course on medical ethics and legal medicine was carefully integrated into the curriculum after some preliminary experiments carried out by a subcommittee which is continually reviewing the situation. Medical ethics has now a definite place in the fourth year, preceded by an introduction to ethical problems encountered in medicine in the first year. Not only do members of the medical faculty participate in this teaching but also members of the faculties of law and the arts.